Determination of public supervision aspects and legal pillars of activities of financial agents in Central European countries - Mikuláš Sidak; Andrea Slezáková; Edita Hajnišová; Stanislav Filip (Administrative Sciences, 2023)
Financial intermediation can be performed by certain types of financial agents or financial brokers in selected European countries. Using primarily analysis and the comparison, the authors focus on certain legal aspects of distribution of financial services in selected Member States of the EU and the EEA, providing a comparative legal analysis. In Slovakia, it is being focused on the subordinate financial agent. The subordinate financial agent is an entrepreneur entitled to perform financial intermediation. The subordinate financial agent belongs under the delegated supervision of the independent financial agent. The paper deals with a consideration de lege ferenda, a change to the relevant legislation according to which the subordinate financial agents could belong to the supervised financial market entities. The authors provide pros and cons regarding the direct supervision of this entity realized by the National Bank of Slovakia. The paper is being prepared by using analysis, synthesis, the inductive method, the deductive method, and the comparative method. When regulating distribution of financial services on the European level, the Insurance Distribution Directive had played a key role. Mainly due to protection of financial consumers, the subordinate financial agent should belong under the direct supervision of the National Bank of Slovakia.
Keywords: 350; Central Bank; distribution of financial services; financial agent; financial broker; financial market supervision